The Gender Binary Within Danish Digital Citizen Identity: An Analysis of Official Websites and MitID - Laufer, David (Culture and History: Student Research Papers, 2025)
In this article, I examine the gender binary present in Danish digital citizen identity through a content analysis of official websites pertaining to the CPR number, Gender reassignment, Name change, and the MitID app. My own experience with MitID app was also used as a data collection method. These forms of categorising Danish citizens in the digital sphere play into the existing gender binary whilst also allowing for its subversion to a certain extent. The analysed texts point to Denmark allowing for a considerable degree of fluidity between genders/sexes, whilst however still enforcing a binary opposition of male and female.